Application Of Economic Mathematics In Periodical Installation System - Ismail, Muhammad Iqbal Al-Banna; Hernawati, Depie; Supena, Yusup (International Journal of Global Operations Research, 2022)
This paper provides financial planning aspect by modeling the impact of mortgage rate changes on the size of payments for ARMS. This study uses a simulation approach to model the choice between a fixed rate mortgage (FRM} and an adjustable rate mortgage (ARM). Our simulations help assess therisks and benefits of choosing an ARM rather than a FRM. We represent the risk of the ARM with distributions of present value cost for a variety of mortgage lifeperiods.